A comparative analysis of pressure sore treatment modalities in community settings - N. Small; M. Mulder; M.J. Mackenzie; M. Nel (AOSIS, 2002)
The management of pressure sores in community settings, poses a clinical problem which challenges the patient's tolerance and the clinician's diligence and ingenuity. Pressure sores can be painful, lead to infection and are associated with considerable morbidity and increased mortality (Patterson & Bennett, 1995:919; Bale, Banks, Hagelstein & Harding, 1998:65). Treatment costs of these wounds are high in terms of resources (Colin 1995:65; Wood, Griffiths & Stoner, 1997:256). However, since there are untold cost in terms of pain and suffering to the patient, it is impossible to calculate the true cost of pressure sores (Dealey, 1994:87).